Pengaruh Pemberian Madu dan Coconut Water Terhadap Penurunan Tekanan Darah Pada Lansia - Nurshinta Handayani; Wahyu Sulfian (KEWINUS: Jurnal Keperawatan dan Kesehatan, 2024)
Hypertension is a non-communicable disease that increases gradually every year around the world. In 2021, mentioned that about 60 elderly people in Tibu village have hypertension experiences. According to the cadres of elderly, many of them in Pustu Tibu Village die due to hypertension and also suffered from heart disease as a result of hypertension. The aim of the research was to obtain the effect of honey with coconut water administered to reduce the blood pressure of the elderly in Tibu Village, Tinombo District. This is quantitative research with a nonequivalent control group design approach. Total of the population about 60 people and samples taken by total sampling technique. Data were analyzed by using the alternative man-Whitney test with honey with coconut water administered as the independent variable and decreasing blood pressure in the elderly as the dependent variable. The results of the pre-test found that most of the elderly (93.3%) in the experimental group respondents have abnormal blood pressure, while the post-test results found that 93.3% of respondents have normal blood pressure results. The results of the bivariate analysis by using the alternative Mann-Whitney test found that have the effect of honey and coconut water were administered to the elderly who had hypertension experiences (p≥α) = 0.00<0.05. The conclusion of the research mentioned that have a significant effect of honey and coconut water were administered to reduce the blood pressure of the elderly in Tibu Village, Tinombo District.